Effects of sexual assault on alcohol use and consequences among young adult sexual minority women - Rhew, Isaac C; Stappenbeck, Cynthia A; Bedard-Gilligan, Michele; Hughes, Tonda; Kaysen, Debra (Journal of consulting and clinical psychology, 2017)
The purpose of this study was to examine effects of sexual assault victimization on later typical alcohol use and alcohol-related consequences among young sexual minority women (SMW). Data were collected over 4 annual assessments from a national sample of 1,057 women who identified as lesbian or bisexual and were 18- to 25-years-old at baseline. Marginal structural modeling, an analytic approach that accounts for time-varying confounding through the use of inverse probability weighting, was used to examine effects of sexual assault and its severity (none, moderate, severe) on typical weekly number of drinks consumed and number of alcohol-related consequences 1-year later as well as 2-year cumulative sexual assault severity on alcohol outcomes at 36-month follow-up. Findings showed that compared with not experiencing any sexual assault, severe sexual assault at the prior assessment was associated with a 71% higher number of typical weekly drinks (count ratio [CR] = 1.71; 95% confidence interval [CI] [1.27, 2.31]) and 63% higher number of alcohol-related consequences (CR = 1.63; 95% CI [1.21, 2.20]). Effects were attenuated when comparing moderate to no sexual assault; however, the linear trend across sexual assault categories was statistically significant for both outcomes. There were also effects of cumulative levels of sexual assault severity over 2 years on increased typical drinking and alcohol-related consequences at end of follow-up. Sexual assault may be an important cause of alcohol misuse among SMW. These findings further highlight the need for strategies to reduce the risk of sexual assault among SMW. (PsycINFO Database Record